A Novel Secure Routing Protocol——Multi-Next Hop Routing Protocl Based on Node Potential - Julong Lan; Jianhui Zhang; Yanhong Wang; Hailong1 Ma; Youjun1 Bu (Dianxin kexue)
Routing protocol is the core network protocol. It is very important to enhancing network availability and security through improving the routing protocol. Based on the research of routing protocol and security mechanism, the concepts of routing potential and credible potential have been defined to characterize the availability and security feature. Furthermore, a novel routing protocol——multi-next hop routing protocol based on node potential was proposed. A good solution was given to deal with the network congestion caused by network unexpected events and the user information safety hazard from unsafe nodes simultaneously. The solution will play an important role to strengthen the network survivability and to safeguard network user information.